Communication skills in Brazilian pharmaceutical education: a documentary analysis - Araújo DC; Santos JS; Barros IM; Cavaco AM; Mesquita AR; Lyra DP Jr (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Objective: To characterize the inclusion of the teaching of communication skills in the curriculum of Pharmacy Schools of Federal Institutions of Higher Education. Methods: An exploratory study of documental analysis of curriculum of Pharmacy Schools was carried out. A convenience sample was selected from undergraduate pharmacy courses of Federal Institutions of Higher Education (IFES). The variables collected were related to the identification of the course, its nature (elective or mandatory), workload, semester, and program content. Results: Among the 49 undergraduate pharmacy courses of IFES, 35 (71.4%) had their curriculum available online. The teaching of communication in health was identified in 26 (74.3%) curriculum. In this study, three courses (7.2%) specifically aimed at teaching communication skills, while 39 (92.9%) had content related to this subject. Most courses (22; 52.4%) belonged to the field of Social, Behavioral, and Administrative Sciences. As for the course period, there was a concentration in the third (19%) and fourth (28.6%) years. The main content present in the curriculum was related to the principles and techniques of health communication (42.8%). Conclusions: Data obtained enabled the identification of gaps in the curricula of undergraduate courses in pharmacy concerning the inclusion of the teaching of communication skills. These results can be used to reflect the current models adopted in Brazil for the teaching of this skills, especially after the recent publication of the new curricular guidelines for undergraduate pharmacy courses.